Targeting multiple myeloma with nanobody-based heavy chain antibodies, bispecific killer cell engagers, chimeric antigen receptors, and nanobody-displaying AAV vectors - Hambach, Julia; Mann, Anna Marei; Bannas, Peter; Koch-Nolte, Friedrich (Frontiers in Immunology, 2022)
Nanobodies are well suited for constructing biologics due to their high solubility. We generated nanobodies directed against CD38, a tumor marker that is overexpressed by multiple myeloma and other hematological malignancies. We then used these CD38-specific nanobodies to construct heavy chain antibodies, bispecific killer cell engagers (BiKEs), chimeric antigen receptor (CAR)-NK cells, and nanobody-displaying AAV vectors. Here we review the utility of these nanobody-based constructs to specifically and effectively target CD38-expressing myeloma cells. The promising results of our preclinical studies warrant further clinical studies to evaluate the potential of these CD38-specific nanobody-based constructs for treatment of multiple myeloma.